2012
DOI: 10.5430/ijhe.v1n2p108
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating the Development of Study Skills through a Blended Learning Approach

Abstract: This study examined the effectiveness of a Blended Learning (BL) environment designed to facilitate the learning of study skills with a large (over 200) and diverse undergraduate student cohort in a Higher Education (HE) institution in the UK. A BL environment was designed using the model provided by Kerres & De Witt (2003), and was also designed to be consistent with Kolb's (1984) experiential learning cycle. Eight focus groups with six students were undertaken to examine student perceptions of their learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…For example, BL has been studied in economics (Zhang, Zhang, & Seiler, 2014), vocational schools (Tsai, Shen, & Tsai, 2011), and science (Oikawa et al, 2013). Benefits of BL over that of traditional courses have included the ability to allow students to study at their own pace (Caulfield, 2011;Linder & E., 2017), improved student outcomes (Means, Toyama, Murphy, Bakia, & Jones, 2010;Tsai et al, 2011), increased student engagement (Baepler, Walker, & Driessen, 2014;Smith, Groves, Bowd, & Barber, 2012) and increased student satisfaction (Martínez-Caro & Campuzano-Bolarín, 2011). Many benefits of BL might be caused by the flipped nature of the environment.…”
Section: Current State Of Blended Learningmentioning
confidence: 99%
“…For example, BL has been studied in economics (Zhang, Zhang, & Seiler, 2014), vocational schools (Tsai, Shen, & Tsai, 2011), and science (Oikawa et al, 2013). Benefits of BL over that of traditional courses have included the ability to allow students to study at their own pace (Caulfield, 2011;Linder & E., 2017), improved student outcomes (Means, Toyama, Murphy, Bakia, & Jones, 2010;Tsai et al, 2011), increased student engagement (Baepler, Walker, & Driessen, 2014;Smith, Groves, Bowd, & Barber, 2012) and increased student satisfaction (Martínez-Caro & Campuzano-Bolarín, 2011). Many benefits of BL might be caused by the flipped nature of the environment.…”
Section: Current State Of Blended Learningmentioning
confidence: 99%
“…Below is the list of some of the existing techniques allowing the teacher to increase efficiency of student time-on-task (18,31):…”
Section: Emphasizing Time-on-taskmentioning
confidence: 99%
“…Similarly, (Lee & Wu, 2006) indicated that the use of videos in web-based computer-mediated communication effectively enhanced pre-service teachers' teaching experience. Moreover, Smith, et al (2012) concluded that the blended learning environment facilitated aspects of experiential learning.…”
Section: Resultsmentioning
confidence: 99%